Teacher training and education programs in Latvia: are e-competences included? - Uzule, Kristine (Business, Management and Economics Engineering, 2020)
Purpose – the purpose of this research is to review the contents of Latvian teacher training and education programs in order to identify if the development of students’ e-competences is included into these programs as an important objective and value. The importance of the development of these competences has been stressed in various EU documents and scientific literature. The scientific importance of the paper lies in gathering evidence for the inclusion of e-competences into teacher training and education curricula and demonstrating that e-competences have not yet acquired a value status in teacher training and education programs. Research methodology – the methodology included the keyword in context and concordance analysis of self-assessment reports and program descriptions, which were run in the software AntConc. Findings – out of 190,000 word tokens, the KWIC analysis identified only 75 entries related to e-competences, most of which included basic skills of information and communication technologies. Other more advanced concepts, such as virtual reality, artificial intelligence, adaptive spaces, e-competences, e-education and e-learning, were hardly mentioned. Research limitations – one limitation of this research is the focus on Latvian teacher training and education programs without their comparison to similar European programs, which would allow for determining the competitiveness of such Latvian programs in Europe. Practical implications – the obtained results suggest that the development of e-competences has not been perceived as value in teacher training and education programs in Latvia, and in order to bridge this gap, programming and artificial intelligence courses should be introduced into the curricula of such programs. Originality/Value – the research has demonstrated that the EU aim of boosting the competitiveness of the European education through the development of e-competences is yet to be implemented into teacher training and education programs in Latvia.